Prediction of follicular thyroid carcinoma associated with distant metastasis in the preoperative and postoperative model. Issue 8 (19th March 2019) - Kim, Hankyul; Shin, Jung Hee; Hahn, Soo Yeon; Oh, Young Lyun; Kim, Sun Wook; Park, Ko Woon; Lim, Yaeji
Abstract: Background: Only clinicopathological findings are reported for predicting follicular thyroid carcinoma (FTC) associated with distant metastasis, and preoperative ultrasound (US) findings are unknown. Methods: Associations between distant metastases of FTC and predicting factors were evaluated by using logistic regression analysis in the preoperative and postoperative models. Results: Distant metastasis was present in 37 (11.5%) of the 321 patients with FTC. In the preoperative model, independent predictors of distant metastasis were age, marked hypoechogenicity, nodule‐in‐nodule appearance, and rim calcification on US. Postoperative predictors were marked hypoechogenicity, rim calcification, and widely invasive histology. Sensitivities, specificities, and the area under the curves for predicting distant metastasis were 86.5%, 80.3%, and 0.889 on preoperative status and 86.5%, 78.5%, and 0.908 on postoperative status. Although not statistically significant, all four patients with gross extrathyroidal extension had metastasis. Conclusion: Age, ultrasound features, and widely invasive histology allow preoperative and postoperative prediction of FTC associated with distant metastasis.